Contamination of Trichloroethylene in Drinking Water System and Its Degradation - Adhikari, Devi Lal; Sato, Chikashi; Lamichhane, Shobha Kanta (Himalayan Physics, 2012)
Photolysis and sonolysis of trichloroethylene (TCE) in water was investigated using a cup-horn, flow-through reactor system. Water containing titanium dioxide was deliberately contaminated with TCE. These solutions were irradiated with ultraviolet light (UV) and ultrasonic waves (US). The decrease in the TCE concentration was observed in water under both US and UV treatments. Present findings declare that the use of UV and US decreased the TCE concentration. With the reactor specifications used, the photolysis and sonolysis processes can produce water meeting the drinking water standard (MCLs of 5?g/L) for TCE. The Himalayan Physics Vol. 3, No. 3 2012 Page : 13-17